Comparative Analysis of Diet Quality Among Junior High School Students Receiving and Not Receiving Free Nutritious Meals in Bogor City - Rahmah; Ikeu Tanziha; Cesilia Meti Dwiriani (Journal of Public Health Sciences, 2026)
Adolescents are a group of people undergoing transitional growth, during which their nutritional needs increase significantly. Based on DQI-A, the diet quality of adolescents aged 13–15 years in Bogor is classified as poor, at only 32.2%. The Free Nutritious Meals (MBG) program aims to ensure that adolescents consistently consume a balanced diet at school. This study aims to analyze the differences in diet quality among junior high school adolescents who are recipients (88 students from SMP PGRI 6) and non-recipients (88 students from SMP PGRI 5) of the free nutritious meals program at school. A cross-sectional comparative design was used involving 176 students selected purposively. Data on individual and family characteristics were collected through structured questionnaires; dietary intake was assessed by two non-consecutive 24-hour recalls conducted by trained interviewers using food photographs and the DQI-A method to measure the quality of the subjects' diets, including dietary quality, dietary diversity, and dietary equilibrium. Data were analyzed using the Mann–Whitney test and the independent-sample t-test. Results showed no significant differences in individual and socioeconomic characteristics between groups (p>0.05). However, significant differences were found in all DQI-A components, including dietary quality, dietary diversity, and dietary equilibrium (p<0.001). The MBG group had a higher average total DQI-A score (49.81%) compared with the non-MBG group (39.15%). These results show that the MBG program helps teens eat better. Recommendations include strengthening the availability and variety of nutritious foods in school meal programs, enhancing nutrition education in schools, and encouraging collaboration among schools, parents, and policymakers. Future researchers are advised to examine the long-term effects of the MBG program on both nutritional status and academic performance.